Investigando os efeitos do contrato didático em uma sala de aula de Matemática: O caso da circunferência e do círculo - Silva, Tony Regy Ferreira da (2016)
This research aimed to analyze the effects of the Didactic Contract discussed by Guy Brousseau in a mathematics classroom of elementary school in the geometry content. This concept, studied by the researcher, presents the clauses in the teaching relationship, which most often are implied, they regulate the expectations and behavior between teacher and student in relation to know the target. So, initially, we conducted a study of the teaching situations, we discuss the concepts of didactical contract, their transgressions and renegotiations, then we focus our discussion on the Didactic Contract effects and then present characteristics of mathematical knowledge, in our case, circles and circles. For this, we follow our methodology, which was conducting observation of classes, when we follow the approach of a math teacher with their students on the knowledge at stake. We analyzed the data collected by checking the existence of effects of the didactical contract. Through our theoretical foundation and the data collected during the research, we find results that indicate the need for reflection on the relations established in the Didactic Agreement and its effects in the classroom. We note also that its prevalence remained to situations involving geometry. We identify elements that show us the emergence of effects from compliance with the rules of behavior governed by the Didactic Contract.